Outcome of Expanded Newborn Screening Among 194 000 Neonates at Northeast México - María del Rosario Torres-Sepúlveda QCB; Laura E. Martínez de Villarreal MD; Jesús Zacarías Villarreal-Pérez MD; María del Consuelo Ruiz Herrera QCB; Patricia del Carmen Arredondo Vázquez MD; Ana Karen Treviño-Morales MD (SAGE Publishing, 2024)
Objectives . To describe the results of a 16-year experience of a state-coverage expanded newborn screening program (NBSP) in Northeast México. Methods . Between 2002 and 2017, dried blood spots of newborns were screened for congenital hypothyroidism (CH), congenital adrenal hyperplasia (CAH), biotinidase deficiency, galactosemia, cystic fibrosis, and glucose-6-phosphate dehydrogenase (G6PD) deficiency via immunofluorescence and amino and fatty acid disorders and organic acidemias using tandem mass spectrometry. Frequency rates were determined. Results . Overall, 192 487 samples were processed; 99.4% had negative results, and 598 were diagnosed. The frequency was 3.01/1000 newborns. G6PD deficiency, CH, amino acidemia, organic acidemia, cystic fibrosis, CAH, fatty acid oxidation disorder, galactosemia, and biotinidase deficiency cases were 1:773, 1:962, 1:4277, 1:4476, 1:11,322, 1:10,693, 1:10,693, 1:38,497, and 1:64,162, respectively. Conclusion . Using different technologies in NBSP increased the number of conditions detected, facilitating infant morbidity and mortality prevention. The frequency of disorders depends on the population's genetic background and diagnostic capacity.